2023
DOI: 10.5114/ceji.2023.126773
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic values of regulatory T cells (Tregs) and Treg-related genes in gastric cancer

Abstract: Introduction:This study attempted to investigate the potential of a risk model constructed for regulatory T cells (Tregs) and their related genes in predicting gastric cancer (GC) prognosis.Material and methods: We used flow cytometry to detect the content of CD4 + CD25 + Tregs. After detecting expression of five Treg-related genes by quantitative real-time polymerase chain reaction (qRT-PCR), Pearson analysis was employed to analyze the correlation between Tregs and related gene expression. 3-( 4,5-dimethylt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…High-density tumor-infiltrating Tregs may promote hepatocellular carcinoma progression and reduce survival by promoting angiogenesis 88 . In addition, Tregs were significantly elevated in the tissues of gastric cancer patients, affecting the survival prognosis of gastric cancer patients 89 . The pRRophetic analysis showed that the high-risk group was sensitive to cytotoxic chemotherapy such as cisplatin and paclitaxel, in contrast to the low-risk group, which was sensitive to gefitinib.…”
Section: Discussionmentioning
confidence: 99%
“…High-density tumor-infiltrating Tregs may promote hepatocellular carcinoma progression and reduce survival by promoting angiogenesis 88 . In addition, Tregs were significantly elevated in the tissues of gastric cancer patients, affecting the survival prognosis of gastric cancer patients 89 . The pRRophetic analysis showed that the high-risk group was sensitive to cytotoxic chemotherapy such as cisplatin and paclitaxel, in contrast to the low-risk group, which was sensitive to gefitinib.…”
Section: Discussionmentioning
confidence: 99%